Physiological damage caused by tooth loss and relationship of nutritional aspects in Pediatric Dentistry (Research, Society and Development, 2021)
The elderly population in Brazil has grown at a fast pace and the dentist must be attentive to expand his knowledge in the field of odontogeriatrics to provide a correct, effective and comfortable treatment for the elderly patient, since they present physiological changes, systemic conditions, psychological and social consequences of the aging process. The purpose of this literature review is to discuss changes in the quality of life of elderly patients, including their emotional reflex and psychological effects. For that, a qualitative research of bibliographic nature from a secondary source was used, an inductive method for the analysis and elaboration of the present work. One of the changes is tooth loss, which has significant effects on the health of the elderly, as it affects masticatory capacity, restricts the consumption of various foods, makes phonation difficult, in addition to aesthetic damage. Malabsorption of nutrients generates a nutritional imbalance with impairment for the realization and maintenance of vital organic processes, greater susceptibility to illnesses and difficulty in recovering from diseases. Adequate nutrition can lead to a healthy old age with greater functional capacity and less incidence of disease, improving quality and lifestyle.